A Comparative Study on Costs and Returns of Native and Recommended Rice Productions in Pak Panang Basin - Dungtripop, Wilawan; Lakkanawanit, Pankeawta (Area Based Development Research Journal, 2018)
This study aims 1) to compare costs and returns between native rice and recommended rice productions in Pak Panang basin, 2) to give suggestions to native rice farmers for improvements of cost-benefit management. The data have been collected from 162 rice farmers in the crop year 2015-2016. The samples of this study consist of 32 Looklai rice farmers, 30 Yumnoon rice farmers, 34 Kapdum rice farmers, 30 Yako rice farmers and 36 recommended rice farmers. The corporation between researchers and farmers during the research process purposely allows knowledge sharing. The farmers have benefited from learning and experiencing ways to calculate the costs and returns of production and ways to reduce costs and increase profits in the future. The comparison of native rices and recommended rice reveals that the costs of native rice per rai range in 12.18 - 265.32 baht lower than the recommended rice, while its profits per rai are 367.03 – 618.61 baht lower. This signifies higher profits of the recommended rice, which is 163.41 baht per rai while most of the native rice varieties face loss. The largest loss is from Yumnoon rice at 433.02 baht per rai. The second and third largest losses are from Yako rice and Kapdum rice at 209.99 and 5.04 baht per rai, respectively. Only Looklai rice shows profits, at 43.54 baht per rai. The recommended ways to increase farmers’ profits are to reduce fixed cost and add product value. Fixed cost of production can be reduced by considering the worthiness of long-term equipment or tools. Product’s added value comes from rice processing with a slight extra cost while giving substantial returns in high product price.